DESAIN IDENTITAS VISUAL PADA UMKM RUANG KERAMIK STUDIO KOTA METRO LAMPUNG - Muhammad Redintan Justin; Rohiman Rohiman; Abdi Darmawan (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
Studio Muljati Ceramic Room sells various types of local ceramics of good quality. However, Ruang Keramik Studio Mulyojati does not have a brand that can give the impression of a strong character in marketing, and can bring out advantages and differences from its competitors. Therefore, this study intends to increase the selling and introduce to the foreign visitors of the Ceramic Studio Room by providing their own brand. This study used a qualitative method with a brainstorming approach and a communication approach. The data analysis used a mind-mapping data analysis. The initial stages of designing the Ruang Keamik Studio logo were done by making alternative sketches, then digitizing them using appropriate visual elements. The result of this study concluded that the concept in designing the identity of the Ceramic Studio Room was